Intratumoral Fibrosis in Facilitating Renal Cancer Aggressiveness: Underlying Mechanisms and Promising Targets - Hu, Chao; Zhao, Yufeng; Wang, Xuanchuan; Zhu, Tongyu (Frontiers in Cell and Developmental Biology, 2021)
Intratumor fibrosis is a histologic manifestation of fibrotic tumor stroma. The interaction between cancer cells and fibrotic stroma is intricate and reciprocal, involving dysregulations from multiple biological processes. Different components of tumor stroma are implicated via distinct manners. In the kidney, intratumor fibrosis is frequently observed in renal cell carcinoma (RCC). However, the underlying mechanisms remain largely unclear. In this review, we recapitulate evidence demonstrating how fibrotic stroma interacts with cancer cells and mechanisms shared between RCC tumorigenesis and renal fibrogenesis, providing promising targets for future studies.